Coregulated human globin genes are frequently in spatial proximity when active - Brown, J; Leach, J; Atzberger, A; Lee-Prudhoe, J; Wood, W; Higgs, D; Iborra, F; Buckle, V; Reittie, J (Rockefeller University Press, 2006)
The organization of genes within the nucleus may influence transcription. We have analyzed the nuclear positioning of the coordinately regulated α- and β-globin genes and show that the gene-dense chromatin surrounding the human α-globin genes is frequently decondensed, independent of transcription. Against this background, we show the frequent juxtaposition of active α- and β-globin genes and of homologous α-globin loci that occurs at nuclear speckles and correlates with transcription. However, we did not see increased colocalization of signals, which would be expected with direct physical interaction. The same degree of proximity does not occur between human β-globin genes or between murine globin genes, which are more constrained to their chromosome territories. Our findings suggest that the distribution of globin genes within erythroblast nuclei is the result of a self-organizing process, involving transcriptional status, diffusional ability of chromatin, and physical interactions with nuclear proteins, rather than a directed form of higher-order control.